In vitro Antiplasmodial Activity and Cytotoxicity of Vincadifformine and Its Semisynthetic Derivatives - M. Mustofa; Michèle Mallié; Alexis Valentin; Guy Lewin (Universitas Gadjah Mada, 2006)
An indole alkaloid with aspidospemane structure possessing a potential antiplasmodial activity, vincadifformine, has been isolated from Aspidosperma pyrifolium Mart. Moreover, 10 derivatives were prepared from the vincadifformine. The study was conducted to evaluate the in vitro antiplasmodial and cytotoxic activity of the vincadifformine and their semisynthetic derivatives. The in vitro antiplasmodial activity was evaluated on Plasmodium falciparum chloroquine-resistant (FcM29) and –sensitive (Nigerian) strains after 24-h and 72-h incubation, while cytotoxic activity was estimated on Hela cells and Cytotoxicity Index (CI = IC50 on HeLa cells/IC50 on FcM29 strain) was calculated to evaluate the safety of tested compounds. Experiment results showed that two compounds (4 and 8) exhibited good antiplasmodial activities in comparison with parent compound, vincadifformine and other tested compounds with IC50 ranging from 5.3 to 12.8 µM on FcM29 strain and 11.4 to 24.0 µM on Nigerian strain. In addition, the CI of two compounds were also lower after 24-h incubation (CI, 2.0 and 4.8) than that of after 72-h incubation (CI, 9.5 and 11.5). Further study will be conducted to evaluate quantitative structure-activity relationship (QSAR) in order to design new antimalarial drugs.